Design and Development of Food Packaging form Betel Husk to add Value for Strong Community and Economic Foundation - Sutthiyapiwat, Somkiat; Phayoonpun, Thammayantee (Princess of Naradhiwas University Journal, 2019)
The aims of this research were to: 1) examine the current use food packaging and identify opportunities for bio-based food packaging from betel husk, 2) verify the quality of betel husk in order to produce Eco-friendly food packaging, 3) invent a bio-based material food packaging machine that works by electrical pneumatics system, and 4) produce food packaging from betel husk. According to a survey, most of local people (83.5%) never perceived that the betel husk can be used as a bio-based food packaging, and that it is heat-resistant (94.6%). The food packaging machine was conceived with an electrical pneumatics system that has an automatic heating control system. The invented food packages were three types including: 1) square plate, 2) circle plate, and 3) cup. Marketing mix 4P’s strategy showed that customers were overall satisfied on quality of the food packages.